Elevated serum levels of adiponectin and interlukin-28B after IFN/RIB therapy in hepatitis C virus-infected patients - Sadeghi, Kaveh; Ahmadi Vasmehjani, Abbas; Baharlou, Rasoul; Hajikhezri, Zamaneh; Kiani, Seyed Jalal (The Journal of Infection in Developing Countries, 2019)
Introduction: The interleukin 28B (IL28B) genotype is associated with changes of lipid metabolism in patients infected with hepatitis C virus (HCV). The association of steatosis with serum levels of adiponectin in chronic hepatitis C (CHC) patients has also been documented. This study aimed for the evaluation of serum levels of IL28B and adiponectin as well as the association of IL28B SNPs with different clinicopathological parameters in HCV-infected patients. Methodology: All 142 HCV-infected patients received peg-interferon plus ribavirin. Detection of rs8099917 and rs12979860 IL-28B genotypes was done with specific primers. Serum IL28 and adiponectin levels were measured using commercial ELISA kits. Results: Higher levels of both IL28 and adiponectin were found in patients. In Genotype 3a (G3a) -infected patients, IL28 and adiponectin serum levels were significantly higher than those infected with G1a. A correlation was found between increasing levels of AST and ALT in G3a-infected patients and the decrease in IL28 and adiponectin serum levels, respectively, in contrast to G1a-infected patients. Higher levels of both IL28 and adiponectin were associated with both CT allele of rs12979860 and TT allele of rs8099917 in patients in comparison with corresponding alleles in controls. Conclusions: In contrast to other studies, this study showed higher serum adiponectin levels in HCV-infected patients compared to that in healthy controls. This finding is possibly due to adiponectin resistance caused by down-regulation of adiponectin receptors or tumorigenic effects of adiponectin. Our genotype-based analyses revealed, at least in part, the involvement of the viral factors in the outcome of HCV infection.